A socio-economic assessment of the impacts of invasive alien plant species on forestry production : the case of Senna spectabilis in Budongo forest reserve, Uganda - Mungatana, Eric D. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.